Museumification of Ani: historical experience and perspectives - Baeva, Olga; Kazaryan, Armen; Samuelyan, Arev (project baikal, 2025)
The article analyzes the problems of museumification of the ruins of the medieval city of Ani. It considers key issues and threats and proposes an integrated approach that combines modern conservation methods, digital technologies, and the development of tourism infrastructure. The necessity of international cooperation for the preservation of Ani as a World Heritage site is substantiated.
Keywords: Ani; museumification; architectural and archaeological complex; conservation; cultural heritage